Inside national health reform - McDonough, John E. (John Edward) (California/Milbank books on health and the public, 2011)
This indispensable guide to the Affordable Care Act, our new national health care law, lends an insider's deep understanding of policy to a lively and absorbing account of the extraordinary--and extraordinarily ambitious--legislative effort to reform the nation's health care system. Dr. John E. McDonough, DPH, a health policy expert who served as an advisor to the late Senator Edward Kennedy, provides a vivid picture of the intense effort required to bring this legislation into law. McDonough clearly explains the ACA's inner workings, revealing the rich landscape of the issues, policies, and con.